DESIGN OF DATABASE BLOCK ON A CONTACTLESS HEART RATE MEASUREMENT SYSTEM USING A CAMERA WITH RPPG TECHNOLOGY - Salman Al Farisyi, Muhammad
The heart rate measurement system using a camera is one of the most widely used research topics today. The use of the camera in this system makes it possible to take heart rate measurements without the need for contact (contactless) with the user. This system utilizes the remote photoplethysmography (rPPG) signal generated by the camera's image capture of the user's body parts, such as the forehead and cheeks. One of the important parts of this system is Database Block. This block serves to store user identity data, user face encoding data generated by the face recognition feature in this system, and user heart rate measurement results. In its implementation, database on this system uses a SQLite database. To facilitate the use of this database in the Python programming language, the sqlite3 module is used. The schema implemented in this database consists of 3 tables, namely the HeartRateData table, the UserProfile table, and the FaceRecogData table. This block has been successfully implemented to perform CRUD functions on user data. This block also features a 256-bit AES encryption security method which is implemented using SQLCipher.